The Societal Costs of Inflation and Unemployment - Olga Popova; Sarah Grace See; Milena Nikolova; Vladimir Otrachshenko (Institute of Labor Economics (IZA), 2023)
What are the broad societal implications of inflation and unemployment? Analyzing a dataset of over 1.9 million individuals from 156 countries via the Gallup World Poll spanning 2005 to 2021, alongside macroeconomic data at the national level, we find that both inflation and unemployment have a negative link with confidence in financial institutions. While inflation is generally unassociated with confidence in government and leadership approval, unemployment still has a strong negative association with these outcomes. While we find no gender differences in the consequences of inflation and unemployment for confidence in political and financial institutions, the associations we document are more substantial for the cohorts that are likely to bear a disproportionate burden from inflation and unemployment—the middle-aged, lower-educated, and unmarried individuals, and for those living in rural areas. Uncertainty about the country's economic performance and one's own economic situation are the primary channels behind the associations we identify. These findings hold significant implications for policymakers, Central Banks, and public discourse, necessitating targeted strategies to alleviate the social consequences of inflation and unemployment.
Keywords: D12; D83; E31; E58; 330; inflation; unemployment; trust; confidence in institutions; Gallup World Poll